Stimulation of Endothelial Progenitor Cells: A New Putative Therapeutic Effect of Angiotensin II Receptor Antagonists - Bahlmann, Ferdinand H.; de Groot, Kirsten; Mueller, Ottfried; Hertel, Barbara; Haller, Hermann; Fliser, Danilo (Hypertension (Dallas, Tex. 1979), 2005)
The number of circulating endothelial progenitor cells (EPCs) correlates with endothelial dysfunction and cardiovascular risk in humans. We explored whether angiotensin II receptor antagonist therapy affects the number of regenerative EPCs in patients with type 2 diabetes. In a prospective double-blind parallel group study, we randomly treated 18 type 2 diabetics with olmesartan (40 mg) or placebo for 12 weeks. We analyzed circulating CD34 hematopoietic progenitor cells (flow cytometry) and EPCs (in vitro assay) before and after therapy. We verified the results in a second open trial treating 20 type 2 diabetics with 300 mg of irbesartan for 12 weeks. The number of EPCs was significantly lower in diabetic patients as compared with 38 age-matched healthy subjects (210±10 versus 258±18 per high-power field; P<0.05), whereas there was no significant difference with respect to hematopoietic progenitor cells. Treatment with olmesartan (n=9) significantly increased EPCs from 231±24 to 465±71 per high-power field (P<0.05), but not hematopoietic progenitor cells. In contrast, placebo treatment (n=9) did not affect EPCs and hematopoietic progenitor cells. With irbesartan therapy, EPC number increased significantly from 196±15 to 300±23 per high-power field (P<0.05) already after 4 weeks of treatment. At the end of 12-week therapy, patients had 310±23 EPCs per high-power field (P<0.05 versus baseline). Angiotensin II receptor antagonists increase the number of regenerative EPCs in patients with type 2 diabetes mellitus. This action may be of therapeutic relevance contributing to their beneficial cardiovascular effects.